Mixed methods process evaluation of an enhanced community-based rehabilitation intervention for elderly patients with hip fracture. Issue 8 (8th August 2018) - Roberts, Jessica Louise; Pritchard, Aaron W; Williams, Michelle; Totton, Nikki; Morrison, Val; Din, Nafees Ud; Williams, Nefyn H
Abstract : Objectives: To describe the implementation of an enhanced rehabilitation programme for elderly hip fracture patients with mental capacity, in a randomised feasibility study compared with usual rehabilitation. To compare processes between the two and to collect the views of patients, carers and therapy staff about trial participation. Design: Mixed methods process evaluation in a randomised feasibility study. Setting: Patient participants were recruited on orthopaedic and rehabilitation wards; the intervention was delivered in the community following hospital discharge. Participants: Sixty-one older adults (aged ≥65 years) recovering from surgical treatment (replacement arthroplasty or internal fixation) following hip fracture, who were living independently prior to fracture and had mental capacity and 31 of their carers. Interventions: Usual care (control) or usual care plus an enhanced rehabilitation package (intervention). The enhanced rehabilitation consisted of a patient-held information workbook, goal-setting diary and up to six additional therapy sessions. Process evaluation components: Recruitment of sites and rehabilitation teams, response of rehabilitation teams, recruitment and reach in patient and carer participants, intervention delivery, delivery to individuals, response of individual patients to the enhanced intervention or usual rehabilitation, response of carer participants, unintended consequences and testing intervention theory and context. Results: Usual rehabilitation care was very variable. The enhanced rehabilitation group received a mean of five additional therapy sessions. All of the returned goal-setting diaries had inputs from the therapy team, and half had written comments by the patients and carers. Focus group themes: variation of usual care and its impact on delivering the intervention; the importance of goal setting; the role of the therapist in providing reassurance about safe physical activities; and acceptability of the extra therapy sessions. Conclusions: Lessons learnt for a future definitive RCT include how to enhance recruitment and improve training materials, the workbook, delivery of the extra therapy sessions and recording of usual rehabilitation care. Trial registration number: ISRCTN22464643 ; Post- results.